Assessment of Surface Roughness of Non-Metallic Materials during Laser Processing - V. A. Alekseev; A. V. Usoltseva; V. P. Usoltsev; S. I. Yuran (Приборы и методы измерений)
Experimental studies of the surface of non-metallic materials have been carried out to determine the roughness parameters of materials such as leather, bone, wood, plastic after processing the surface of materials with a laser beam. To assess the quality of the surface layer of materials, the depth of penetration of laser radiation into the material, the average value of the micro unevenness, and the mean square deviation of the micro unevenness were used. To describe the changes in the values of the micro unevenness, graphs of the correlation of the parameters of the micro unevenness and the modulus of elasticity of the surface of various non-metallic materials were used. Approximating polynomials are used to describe the correlations with the representation in a computer. A regression model is proposed that relates the properties of the material to the magnitude of the micro unevenness. Data on the depth of ablation for wood, bone, leather, plexiglass are presented, graphs of the correlation between the amount of surface micro unevenness and the density of materials, between the amount of surface micro-roughness and the modulus of elasticity of materials, the correlation coefficient between the amount of surface micro unevenness and the ignition temperature of organic materials. The obtained models make it possible to implement the proposed principle of laser processing of non-metallic materials, which consists in measuring the modulus of elasticity of the surface of the material and, based on the measurements obtained, control the modes of laser processing of products. The installation of laser surface treatment of non-metallic materials with the implementation of the principle of control of processing modes depending on the measured values of the modulus of elasticity of the surface of the material is proposed. To measure the elastic modulus of a material, a special sensor is used with indentation of the indenter and computer evaluation of the measurements obtained with the formation of solutions for controlling the modes of laser surface treatment of the material. The experimental results obtained made it possible to manufacture a number of products to ensure a given surface quality of non-metallic materials (a writing device, a gift for the newlyweds). Conducting experiments with changes in the power of laser radiation based on the results of measuring the modulus of elasticity of the surface of non-metallic materials has shown the effectiveness of operational setting of laser operating modes to ensure the quality of the surface of non-metallic materials.